Explicit versus implicit understanding of teaching: Does knowing what teaching is help children to learn from it?. (April 2018) - Jeong, Jeein; Frye, Douglas
Abstract: One hundred and sixteen Korean 3- to 5-year-olds were individually taught animal names through a game, either in a direct condition in which the instructional goal was stated or an indirect condition in which it was not. How much they learned and how well they understood the intentionality of teaching were also measured. Korean children seemed to have relatively rapid development in understanding of the intentionality of teaching, and this understanding was correlated with their identification of the goal of the game. The direct condition produced better learning for the children who had higher understanding of the intentionality of teaching. Highlights: Korean children come to understand intentionality of teaching in early childhood. Korean children seem to have relatively early development of this understanding. Knowing intentionality of teaching helps children identify the goal of instruction. Explicit understanding of teaching influences their learning in direct teaching.